Ensuring safety in soy: a review of chlorpyrifos detection and mitigation for consumer confidence - Ziemann-Bolinske, Shaundra (My University, 2025)
With growing consumer interest in food production and processing, understanding how agricultural practices balance profitability with food safety is crucial. The agricultural industry utilizes various methods to ensure crop success, including pesticide use. Chlorpyrifos (CPF), a widely used pesticide, remains under regulatory scrutiny due to concerns about its safety and environmental impact. After alternating between federal approvals and restrictions, the United States (U.S.) Environmental Protection Agency (EPA) authorized CPF for use on soybeans in February 2024. This shifting regulatory stance highlights the need to accurately identify CPF residues on soybeans and evaluate both natural and processing mitigation factors to reduce their presence. This report evaluates the efficacy of removing chlorpyrifos by naturally occurring environmental factors, such as storage time and sunlight exposure, as well as interventive processes—washing with water, ultrasound (ULS), ozone (O3), heat application, and cold plasma treatment—on the food safety of soybeans. Additionally, the importance of a multi-step approach is emphasized for effectively reducing CPF residues, as storage or heat processing alone often do not meet safety thresholds. Cold plasma (CP) resulted in surface damage to the beans, rendering the process unacceptable, although faster to reach tolerance levels than O3. While washing and O3 treatments demonstrated moderate success, a combination of ULS and O3 treatments demonstrated synergistic effects in reducing CPF concentrations on soybeans.
Keywords: Chlorpyrifos; Organophosphate; Pesticide degradation; Soybean; Pesticide mitigation; Consumer confidence